2002
DOI: 10.1128/jb.184.7.1916-1924.2002
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Alcohol Dehydrogenases Participate in Butane Metabolism byPseudomonas butanovora

Abstract: The involvement of two primary alcohol dehydrogenases, BDH and BOH, in butane utilization in Pseudomonas butanovora (ATCC 43655) was demonstrated. The genes coding for BOH and BDH were isolated and characterized. The deduced amino acid sequence of BOH suggests a 67-kDa alcohol dehydrogenase containing pyrroloquinoline quinone (PQQ) as cofactor and in the periplasm (29-residue leader sequence). The deduced amino acid sequence of BDH is consistent with a 70.9-kDa, soluble, periplasmic (37-residue leader sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 46 publications
1
49
0
2
Order By: Relevance
“…The fatty acid alcohols generated by terminal oxidation of n-alkanes were further oxidized to aldehydes by ADHs and similarly as reported from Bacillus sp., P. butanovora and G. thermodenitrificans NG80-2 (Li et al 2008;Vangnai and Arp 2001;Vangnai et al 2002). Thus, the ADHs were essential for growth of microorganisms in the presence of nalkanes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The fatty acid alcohols generated by terminal oxidation of n-alkanes were further oxidized to aldehydes by ADHs and similarly as reported from Bacillus sp., P. butanovora and G. thermodenitrificans NG80-2 (Li et al 2008;Vangnai and Arp 2001;Vangnai et al 2002). Thus, the ADHs were essential for growth of microorganisms in the presence of nalkanes.…”
Section: Discussionmentioning
confidence: 98%
“…Alcohols generated by terminal oxidation of n-alkanes are further oxidized to aldehydes by ADHs, therefore, provide complete biotransformation. Similar to AHy, there are few microbes that can excrete four different ADHs with species specificity, i.e., towards primary and secondary alcohols (Vangnai and Arp 2001;Vangnai et al 2002). Therefore, the degradation efficiency and intermediate products from degradation of long-chain hydrocarbons and n-alkanes rely on the type of isolate used and their enzymatic oxidation properties.…”
Section: Introductionmentioning
confidence: 99%
“…Further metabolism probably proceeds via β-oxidation [128]. Gene disruption experiments demonstrated the involvement of two primary alcohol dehydrogenases (BOH and BDH) in the n-butane utilization [133].…”
Section: Butane Monooxygenase (Bmo) In Pseudomonas Butanovoramentioning
confidence: 99%
“…grown on or induced with short-chain-length alcohols, while the induction of ADH-IIG is mainly restricted to 1,2-propanediol (Toyama et al, 1995). P. putida HK5 is one of only two organisms reported so far that expresses more than one type of PQQ-ADH in response to exposure to alcohols (Vangnai et al, 2002). Therefore, it is interesting to examine how the expression of the three enzymes is distinguished and regulated at a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Although considerable research has been carried out on the biochemistry and physiology associated with the qADHs (Anthony & Williams, 2003;Chen et al, 2002;Matsushita et al, 1999;Toyama et al, 2004), much less is known about the transcriptional regulation of these enzymes. Insights into the complexity of the transcriptional regulation of qADHs have been obtained from studies of Pseudomonas aeruginosa (Gliese et al, 2004), Pseudomonas butanovora (Vangnai et al, 2002), Pseudomonas putida (Promden et al, 2008) and Methylobacterium extorquens, in which at least 28 genes have been shown to be involved in the oxidation of methanol to formaldehyde (Lidstrom et al, 1994;Springer et al, 1995). In P. aeruginosa, the transcription of a quinoprotein ethanol dehydrogenase (qEDH) promoter, namely the exaA promoter, is regulated by a two-component system: a histidine sensor kinase (ExaD), which is presumably located in the cytoplasm, and a response regulator (ExaE).…”
Section: Introductionmentioning
confidence: 99%